Does extremity-MRI improve erosion detection in severely damaged joints? A study of long-standing rheumatoid arthritis using three imaging modalities. Issue 11 (31st July 2007) - Freeston, J E; Conaghan, P G; Dass, S; Vital, E; Hensor, E M A; Stewart, S; Emery, P
Abstract : Background: Long-standing rheumatoid arthritis produces unique challenges when assessing damage due to joint deformity. The use of extremity magnetic resonance imaging (eMRI) offers the possibility of improved disease assessment because of greater patient tolerability. Objectives: The aim of this cross-sectional study was to compare the identification of wrist erosions in a severe rheumatoid arthritis cohort by eMRI with a restricted field of view (eMRI-RV) to radiography and high field MRI, using the latter as the reference. Methods: Fifteen patients (87% female, median age 56 years) with active rheumatoid arthritis (median DAS28 7.01 and disease duration 11 years) on leflunomide were enrolled. Radiography of hands, eMRI-RV (0.2 T MagneVu MV 1000) and high field MRI of unilateral wrist joints were performed. Results: Of 86 comparable wrist joint areas, high field MRI identified 70 erosions, eMRI-RV 32 and radiography 4. With high field MRI considered the reference, the sensitivity, specificity and accuracy of eMRI-RV for erosions were 46%, 94% and 55%, and the corresponding values for x ray were 6%, 100% and 23%, respectively. Conclusions: In severely damaged rheumatoid arthritis joints, sensitivity of erosion detection was markedly higher for eMRI-RV than radiography, using high field MRI as the reference. eMRI-RV was, however, less sensitive than high field MRI.